2021
DOI: 10.1021/acs.joc.1c00853
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Gly-Ψ[CH(CF3)NH]-Peptides

Abstract: The solid-phase synthesis of Gly-Ψ[CH(CF 3 )NH]-peptides is presented. In order to achieve this goal, the synthesis of Gly-Ψ[CH(CF 3 )NH]-dipeptides having the C-terminus unprotected, the N-terminus protected as Fmoc- or Teoc-, and possibly side chain functionalities protected with acid-labile protecting groups has been developed. A selected small library of six peptidomimetics, encompassing analogues of biological relevant peptides, have been obtained in high puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A series of research devoted to the stereoselective aza‐Michael addition of chiral α‐amino acid esters to β‐fluoroalkylnitroalkenes was carried out by Prof. Volonterio's scientific team [106–111] . It was shown that the ( E )‐3,3,3‐trifluoro‐1‐nitropropene 115 a is a good starting material for the synthesis of Gly‐Ψ[CH(R F )NH] peptides.…”
Section: Aza‐michael Reactions With Other Pull‐pull Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of research devoted to the stereoselective aza‐Michael addition of chiral α‐amino acid esters to β‐fluoroalkylnitroalkenes was carried out by Prof. Volonterio's scientific team [106–111] . It was shown that the ( E )‐3,3,3‐trifluoro‐1‐nitropropene 115 a is a good starting material for the synthesis of Gly‐Ψ[CH(R F )NH] peptides.…”
Section: Aza‐michael Reactions With Other Pull‐pull Alkenesmentioning
confidence: 99%
“…A series of research devoted to the stereoselective aza-Michael addition of chiral α-amino acid esters to β-fluoroalkylnitroalkenes was carried out by Prof. Volonterio's scientific team. [106][107][108][109][110][111] It was shown that the (E)-3,3,3-trifluoro-1-nitropropene 115 a is a good starting material for the synthesis of Gly-Ψ[CH-(R F )NH] peptides. The addition of α-amino esters, generated in situ from the corresponding hydrochloride salts 120 in the presence of a base, proceeded in the expected way: the nucleophilic attack was directed on the carbon bearing CF 3 moiety (Scheme 47).…”
Section: Aza-michael Reactions With Other Pull-pull Alkenesmentioning
confidence: 99%